2015
DOI: 10.3758/s13423-015-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability and stability in the McGurk effect: contributions of participants, stimuli, time, and response type

Abstract: In the McGurk effect, pairing incongruent auditory and visual syllables produces a percept different from the component syllables. Although it is a popular assay of audiovisual speech integration, little is known about the distribution of responses to the McGurk effect in the population. In our first experiment, we measured McGurk perception using 12 different McGurk stimuli in a sample of 165 English-speaking adults, 40 of whom were retested following a one-year interval. We observed dramatic differences both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
174
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(194 citation statements)
references
References 40 publications
16
174
4
Order By: Relevance
“…Accuracy rates were calculated for the congruent, auditory-alone, and visual-alone stimulus conditions, and differences in accuracy rates across groups and across conditions within each group were assessed using appropriate nonparametric tests given concerns about violations of the normality and homogeneity of variance assumptions underlying parametric tests for these data [63]. Visual bias (the McGurk effect) in each of the incongruent conditions was defined as the percentage of trials in which participants made either a visual or combination response.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy rates were calculated for the congruent, auditory-alone, and visual-alone stimulus conditions, and differences in accuracy rates across groups and across conditions within each group were assessed using appropriate nonparametric tests given concerns about violations of the normality and homogeneity of variance assumptions underlying parametric tests for these data [63]. Visual bias (the McGurk effect) in each of the incongruent conditions was defined as the percentage of trials in which participants made either a visual or combination response.…”
Section: Data Analysesmentioning
confidence: 99%
“…The strength of the McGurk effect (i.e., the likelihood that incongruent visual speech information influences the perception of auditory speech information) varies considerably across different audiovisual combinations, due primarily to the differences in the relative perceptual reliability of the auditory and visual components of the McGurk stimuli [63,64]. Strong McGurk stimuli occur when the visual component is more reliable than the auditory component and is therefore given greater weight in the integration process, thereby facilitating integration of the visual input with the auditory input to create a strong McGurk effect.…”
Section: Introductionmentioning
confidence: 99%
“…Using empirical data and simulations, we show that high within-group variability, coupled with routine use of small sample sizes, leads to a proliferation of inflated estimates of group differences in multisensory integration. Our results explain why recent studies have failed to replicate the large reported differences between cultures(15), genders (13), and children with developmental disorders (16). Studies of multisensory integration must increase sample sizes by an order of magnitude to produce accurate and reliable estimates of group differences.…”
Section: Introductionmentioning
confidence: 62%
“…As a behavioral assay, susceptibility to the McGurk effect has been used to argue for important differences in multisensory integration between genders(5), in atypical human development(4, 6), across the lifespan(7), in mental health disorders (8,9), and between cultural/linguistic groups (10)(11)(12). Amidst the enthusiasm for using the McGurk effect to study such between-group differences, recent work has highlighted large within-group variability in susceptibility to the illusion using relatively homogeneous subject pools (13,14). However, most studies of the McGurk effect test a relatively small number of participants, with only a single published study reporting a group size of greater than 100 (15).…”
Section: Introductionmentioning
confidence: 99%
“…This variability in response is certainly not unique to speech perception-production interaction. For instance, the McGurk effect, a traditional measure of audiovisual integration and well known in the DD field, shows a dramatic diversity of responses both across individuals and across used stimuli (Mallick, Magnotti, & Beauchamp, 2015).…”
Section: Phonological Representations and The Role Of Altered Auditormentioning
confidence: 99%